2019
DOI: 10.1101/838896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A screening platform based on epitope editing for drug discovery

Abstract: The interaction between an antibody and its epitope has been daily utilized in various biological studies; however it has been rarely explored whether small molecules can alter the interaction. We discovered that small molecules could alter/edit surface properties of amyloid beta (Aβ) epitopes, and consequently inhibit or enhance corresponding antibody recognition. Remarkably, this editing effect could generate functional changes including protein aggregation behaviors, cell cytokine secreting and in vivo micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Recently, our group demonstrated that small molecules could alter epitope binding to its antibody, resulting in enhanced or weakened binding of the antibody to its antigen. We found that this epitope alteration could be used as a screening platform for the discovery of drug (we termed this s creening p latform based on e pitope alt e ration for d iscovery as SPEED) . To investigate whether SHA-2 has this alteration effect, we incubated Aβ40 monomers with and without SHA-2, and Aβ40 antibody 4G8, whose binding epitope is the hydrophobic Leu17–Val24 segment, was used in our dot-blotting assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group demonstrated that small molecules could alter epitope binding to its antibody, resulting in enhanced or weakened binding of the antibody to its antigen. We found that this epitope alteration could be used as a screening platform for the discovery of drug (we termed this s creening p latform based on e pitope alt e ration for d iscovery as SPEED) . To investigate whether SHA-2 has this alteration effect, we incubated Aβ40 monomers with and without SHA-2, and Aβ40 antibody 4G8, whose binding epitope is the hydrophobic Leu17–Val24 segment, was used in our dot-blotting assay.…”
Section: Resultsmentioning
confidence: 99%
“…We found that this epitope alteration could be used as a screening platform for the discovery of drug (we termed this screening platform based on epitope alteration for discovery as SPEED). 52 To investigate whether SHA-2 has this alteration effect, we incubated Aβ40 monomers with and without SHA-2, and Aβ40 antibody 4G8, whose binding epitope is the hydrophobic Leu17−Val24 segment, was used in our dot-blotting assay. From Figure 3a, it is clear that SHA-2 can significantly weaken the binding between Aβ40 and 4G8 antibody, suggesting that SHA-2 can bind to the hydrophobic environment in Aβ40 peptides.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Recently, our group demonstrated that small molecules could alter epitope binding to its antibody, resulting enhanced or weakened binding of the antibody to its antigen. 40 To investigate whether SHA-2 has this alteration effect, we incubated Aβ monomers with and without SHA-2, and Aβ antibody 4G8 (epitope Leu17-Val24) was used in our dot-blotting assay. From Fig.3a, it is clear that SHA-2 can significantly weaken the binding between Aβ and 4G8 antibody, suggesting that SHA-2 can bind to Aβ peptides.…”
Section: Dynamic Binding Sites Of β-Amyloid Peptides Tailor Sha-2 Swimentioning
confidence: 99%